Cedar and cypress pollen counts are associated with the prevalence of allergic diseases in Japanese schoolchildren. Issue 6 (29th April 2013) - Yoshida, K.; Adachi, Y.; Akashi, M.; Itazawa, T.; Murakami, Y.; Odajima, H.; Ohya, Y.; Akasawa, A.
Abstract Background Patients allergic to pollen have been known to become more symptomatic during pollen season compared with the nonpollen season. However, there are few studies regarding whether higher exposure to pollen might increase the prevalence of allergic diseases. Methods An ecological analysis was conducted to evaluate whether pollen exposure is associated with the prevalence of allergic diseases in schoolchildren. Pollen count data of Japanese cedar (Cryptomeria japonica) and Japanese cypress (Chamaecyparis obtusa), which are the major pollen allergens in Japan, were obtained from each prefecture. The prevalence of allergic diseases in schoolchildren in each prefecture was based on a nationwide cross‐sectional survey using the International Study of Asthma and Allergies in Childhood questionnaire. Results After omitting three prefectures where pollen data were not available, data of 44 prefectures were analysed. The prevalence of allergic rhinoconjunctivitis in children aged 6–7 years was positively associated with both cedar and cypress pollen counts (P = 0.01, both), whereas the prevalence of allergic rhinoconjunctivitis in children aged 13–14 years was positively associated with only cypress pollen counts (P = 0.003). Furthermore, the prevalence of asthma was positively associated with cedar pollen counts in 6‐ to 7‐year‐old children (P = 0.003) but not cypress pollen counts in either age group. Conclusions There are ecological associations between pollen counts and the prevalence of allergic diseases in Japanese schoolchildren. Further studies are needed to determine whether the difference between the effects of cedar and cypress pollens is attributable to pollen counts or allergenicity.